Pengaruh Model Pembelajaran Sains Teknologi Masyarakat dalam Meningkatkan Motivasi Belajar Kimia pada Materi Koloid - Lusi Wulandari; Zona Octarya (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research was instigated with the low of student chemistry learning motivation. It aimed at finding out whether there was a difference of chemistry learning motivation between students taught by using Science Technology Society learning model and those who were not taught by using Science Technology Society learning model. It was quantitative research with quasi-experiment method. The samples of this research were the eleventh-grade students of MIA 2 and 4, and they were 72 students. Questionnaire and documentation were used to collect data. Independent sample t-test was the technique of analyzing data. Based on data analysis results, there was a difference of chemistry learning motivation between students taught by using Science Technology Society learning model and those who were taught by using conventional learning model on Colloid lesson at State Islamic Senior High School 3 Pekanbaru. It was proven with the score of tobserved higher than ttable at 5% significant level (4.587>1.994). Based on the result of effect size test by using Cohen’s formula, the score of d 2.59 was lower than 1, and it meant that Science Technology Society learning model affected student chemistry learning motivation significantly.